南極ドームふじ近傍の氷床の環境 - 氷床から完新世（ホロシーン）の層を取り除くと氷期LGMのドーム位置が見える - - 藤田, 秀二 (2017)
南極ドームふじ近傍は、Oldest Ice （100万年を上回る年代をもつ最古のアイスコア）の掘削候補地として着目されている地域である。日本の南極観測では、1980年代からこの近傍のアイスコア研究と雪氷環境研究にダーゲットをしぼった観測研究をおこない、1990年代と2000年代にわたり２本の深層アイスコアを取得した。Oldest Iceの掘削候補地の同定には、氷床表面環境、内部環境、底面環境の入念な観測とデータの検討が必要である。これまでこの地域で日本が実施してきた観測データをコンパイルし、氷床内部層の３次元構造の分析をすすめている。その結果、氷床内部に蓄積された歪みのパターンは、現在のドームふじの南方に過去のドームがあることを示唆した。さらに、最終氷期のLGM以降に堆積した雪の量は、強い南北勾配（北方ほど堆積が多い）をもつことがわかった。最終氷期の当年代面を氷床表面とした地形図を作成すると、氷期の氷床ドームは現在のドームふじの南方約60kmの、我々が通称新ドームふじ (New Dome Fuji: NDF)と呼ぶ地域近傍に出現した。コロキではデータ分析の最新状況を示す。 Dome Fuji in East Antarctica is one of candidate areas for finding sites of "Oldest Ice" that has age beyond 10^6 years. In the Japanese Antarctic research program, this area was surveyed for long years since 1980's, focusing on glaciological study and ice core study. Two deep ice cores were drilled, once in 1990's and another in 2000's. For identification of proper sites for the oldest ice, we need to examine information of surface, internal and bottom conditions of the ice sheet. I am currently compiling data of radar sounding historically in this area. Main results are as follows.Strain pattern accumulated within the ice sheet was examined. The data was explainable if we assume that the dome summit was located in the south in the past. In addition, snow deposition after the last glacial maximum (LGM) has steep spatial gradient; northern side has more accumulation rate. Contour map of the LGM surface of the ice sheet had highest summit in ~60 km south of present Dome Fuji, where we call the area as New Dome Fuji (NDF). I will show latest output of the data analysis. Polar Meteorology and Glaciology Group seminar / 気水圏コロキウム 日時：2月8日（水）10:00-10:50 場所：C301（3階セミナー室） conference object